Phenotype and genotype analyses of Chinese patients with autosomal dominant mental retardation type 5 caused by SYNGAP1 gene mutations - Wang, Yanxin; Lv, Yuqiang; Li, Zilong; Gao, Min; Yang, Xiaomeng; Li, Yue; Shi, Jianguo; Gao, Zaifen; Liu, Yi; Gai, Zhongtao (Frontiers in Genetics, 2022)
Background Autosomal dominant mental retardation type 5 (MRD5), a rare neurodevelopmental disorder (NDD) characterized by intellectual disability (ID), development delay (DD) and epilepsy predominantly, is caused by heterozygous mutation in the SYNGAP1 gene. SYNGAP1 mutations have been rarely reported in the Chinese population. Here, we present an investigation of SYNGAP1 mutations in a clinical cohort with ID and DD in Shandong, a northern province in China to further explore the genotype and phenotype correlations. Methods A retrospective study was conducted for 10 children with SYNGAP1 mutations presenting ID, DD and epilepsy who were diagnosed between January 2014 and May 2022. Clinical data and genetic tests were collected. Treatment and regular follow-ups were carried out to pay close attention to the prognosis of the patients. Results We described 10 unrelated affected individuals with SYNGAP1 mutations, displaying ID, DD, epilepsy or seizures. All mutations of SYNGAP1 in the 10 patients were de novo except patient 3 whose father was unavailable, including 5 nonsense mutations, 2 frameshift mutations, 2 splicing mutations and 1 codon deletion. Among these mutations, 5 were novel and the other 5 were previously reported. Significantly, all patients with epilepsy were sensitive to anti-seizure drugs, especially sodium valproate. Furthermore, rehabilitation training seemed to exert a more improved effect on motor development than language development for the patients. Conclusion The 10 patients carrying SYNGAP1 mutations were diagnosed as MRD5. Five novel genetic mutations were found, which expanded the mutational spectrum of the SYNGAP1 gene. The identification of these mutations in this study helps explore the relationship between genotypes and phenotypes, and contributes to genetic counseling and therapeutic intervention for patients with MRD5.